Application of Hydrocolloids as Coating Films to Reduce Oil Absorption in Fried Potato Chip-Based Pellets - Ajo, Radwan Yousef (Pakistan Journal of Nutrition, 2017)
Background and Objective: Fat frying is a popular method used in food processing. Potato chip-based pellets (PCBPs) are the most commonly consumed fried food item manufactured globally. Due to increased consumer awareness surrounding the health problems associated with consumption of high-fat fried foods, preferences have shifted to fried food that is lower in fat. The present study aimed to investigate the effects of using carrageenan and xanthan thin coating films to reduce oil absorption in fried potato chip-based pellets and to evaluate the chemical, physical and sensory properties of the resulting products. Materials and Methods: In the present study, two selected hydrocolloids of different concentrations, carrageenan (1, 2, 3 and 4%) and xanthan (0.1, 0.2, 0.3 and 0.4%), were used to coat potato chip-based pellets to evaluate their effect on moisture retention, oil absorption reduction and sensory characteristics. Results: Carrageenan and xanthan significantly reduced oil absorption across all concentrations, ranging from 24-46.9% and 25.6-57.4%, respectively. The most effective level of fat reduction was found using 4% carrageenan and 0.3% xanthan coatings. Overall sensory acceptability was improved across concentrations. Conclusion: Application of edible coatings to reduce oil content can be used to produce products that meet the health and quality preferences of consumers.